Zeliščarstvo kot poslovna dejavnost na podeželju - Gornik, Barbara (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2019)
In the last twenty years, herbalism has become a multifunctional production and service activity in which entrepreneurship, traditional knowledge, agriculture, environmental protection and modern lifestyles are intertwined. A key, relatively new player in Slovenian herbalism are herbal entrepreneurs, who enter the market with different knowledge and marketing approaches. Qualitative analysis of semi-structured interviews with herbal entrepreneurs produced a qualitative profile for each company and a schematic representation of entrepreneurial and marketing characteristics (diversity of offer, sales channels, opportunity for expansion of of-fer, promotion, networking, availability of workforce and succession issue). They are highly dependent on the characteristics of the operator, namely his or her age, completed formal education, age of the company and entrepreneurial experience, and the reasons for establishing the company. For the successful operation of herbal entrepreneurs their connection with the local and wider (business) environment is of essential importance.
Keywords: herbalism; podeželje; podjetništvo na podeželju; razvoj podeželja; rural areas; rural development; rural entrepreneurship; Slovenia; Slovenija; zeliščarstvo